Analysis of the heat exchange processes of the remote measurement device of mechanical values - Halytskyi, Viacheslav (Technology audit and production reserves, 2018)
The object of research is a model of the thermal state of a remote measurement device, determined by the operating conditions and caused by the need to confirm the operation of the device in ambient conditions according to the requirements of the specification. During the research, the physical formulation of the problem of determining the thermal state of a remote measurement device under various operating conditions and their mathematical description were used. The choice of strategy is based on the solution of technological problems that ensure the optimal process of control. The thermal and mathematical model of the thermal mode of the device is developed to calculate the multidimensional temperature fields of the elements of the device. The model of the thermal mode of the remote measurement device is obtained. The proposed method allows to determine the temperature regimes of the nodes in the preparation mode and the main work at different ambient temperatures. In particular, determine the emitting power at the design state and changes over time. The model takes into account the geometric parameters of the main structural elements of the device. At the same time, in order to maintain the heat balance and the adequacy of the model to the main elements of the device, additional characteristics of these components are introduced in the mathematical model. So, the radiation heat exchange between the external surfaces of the device and the compartment structures surrounding it is taken into account. The regularity of changes in ambient temperature depending on the operation mode of the device is taken into account. The non-stationary thermal state of a remote measurement device is considered, taking into account the radiation-convective heat exchange of the external surfaces of the device with the environment. According to the conducted studies, the thermophysical characteristics of the materials used in the model are determined with two options of the temperature conditions of operation of the remote measurement device. The model is implemented in the STAR-CCM program code based on the control volume method. This technique simplifies the development of a numerical three-dimensional model from the control volumes of a remote measurement device for computer analysis. These studies are an integral part in the design, development and use of a remote measurement device based on a gyro sensor in various temperature conditions.